The terrible two eaudiobook - Barnett, Mac (Terrible Two, 2015)
Miles Murphy had it made. He lived in a great town near the ocean, he had two best friends, and most importantly, he had a reputation for being his town's best prankster. All of which explains why he's not happy to be moving to Yawnee Valley, a sleepy town that's famous for one thing and one thing only: cows. Worse than that, Miles quickly discovers that Yawnee Valley already has a prankster—and a great one. If Miles is going to take the title from this mystery kid, he'll have to raise his game. It's prankster against prankster in an epic war of trickery, until the two finally decide to join forces to pull off the biggest prank ever seen, a prank so huge it would make the members of the International Order of Disorder (a loose confederacy of pranksters that flourished a couple of centuries ago) proud. In The Terrible Two , bestselling authors and friends Jory John and Mac Barnett have walked an impressive tightrope, creating a series that has its roots in classic middle-grade literature yet feels fresh and daring at the same time.